2020
DOI: 10.21203/rs.3.rs-46000/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific Dynamic Variations in the Peripheral Blood Lymphocyte Subsets in COVID-19 and Severe Influenza a Patients: A Retrospective Observational Study

Abstract: Background: Both COVID-19 and influenza A contribute to increased mortality among the elderly and those with existing comorbidities. Changes in the underlying immune mechanisms determine patient prognosis. This study aimed to analyze the role of lymphocyte subsets in the immunopathogenesisof COVID-19 and severe influenza A, and examined the clinical significance of their alterations in the prognosis and recovery duration. Methods: By retrospectively reviewing of patients in four groups (healthy controls, sev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Qian et al [17] agrees with the current study as they reported association between COVID-19 severity and old age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Qian et al [17] agrees with the current study as they reported association between COVID-19 severity and old age.…”
Section: Discussionsupporting
confidence: 93%
“…Qian et al [17] and Khamiss et al [19] also studied comorbidities among COVID-19 patients; hypertension and diabetes were the most frequent co-morbidity followed by COPD and cardiovascular diseases which was similar to the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown that the majority of the COVID‐19 patients can present with fever, cough, fatigue, headache, myalgia, and severe respiratory disease 6–8 . The most common manifestations of COVID‐19 patients are almost similar to SARS and MERS 9 .…”
Section: Introductionmentioning
confidence: 99%